(untitled) (Nigerian Journal of Technology, 2024)
Inadequate knowledge of equipment and operations control ratios which contribute largely to low process capacity in the de-husking lines of small-scale rice processing factories is one of the critical challenges to improving rice processing in Sub-Saharan African countries, particularly Nigeria where capacity deficit leads to rice importation. This study seeks to empirically investigate equipment and operations control ratios in de-husking lines of small-scale factories in order to explore their potential and improve process capacity. The objectives are to determine the equipment and operations effectiveness, identify the root causes of inefficiency, and prioritize improvement efforts in the de-husking lines. The study was carried out in 10 selected factories of a milling cluster where production data for 2017-2022 was collected to complement data obtained through direct observation during processing hours and structured interviews. Microsoft Excel and Scilab software were used for data analysis based on existing models and other mathematical models developed for this study. Fluctuations observed in the process capacities of the de-husking lines from 2017-2022 indicated variabilities in equipment availability and performance. The overall equipment effectiveness (OEE) was generally below 50% which indicates production losses caused by frequent downtime and reduced speed of the machines. The overall operations effectiveness (OOE) were below 40%, and that implies the de-husking lines do not respond well to unscheduled downtime or unexpected tasks to reduce downtime for process capacity improvement. Tracing other potential to be unlocked to improve process capacity with the existing machines in the de-husking lines; the total effective equipment performance (TEEP) values were found below 25%, leaving 75% potential to be unlocked. Reliability modelling before machine installation, preventive maintenance, extended work scheduling, continuous training of workforce to reduce delays in equipment repairs are some of the measures to increase machine availability and improve process capacity in de-husking lines of small-scale rice processing factories.